2012
DOI: 10.1097/sih.0b013e3182611844
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Virtual Reality Simulation for Obstetric Ultrasonography

Abstract: Clinicians with differing ultrasonography expertise showed differing skill with the UltraSim VR simulator, demonstrating construct validity for skills needed in simulation. Consideration should be given to investigating whether trainees with minimal scanning experience can improve their clinical skills and efficiency with VR simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…7 There is supportive literature on the usefulness of OB GYN US simulation that reveals it not only improves the scanning skills and detection rates of abnormal fi ndings but also helps providers to maintain their skills. [7][8][9][10] The results of our workshop suggest that virtual reality pelvic US simulation used in conjunction with didactics may improve the systematic approach in US scanning. A limitation of our study is that it refers to the outcomes of a single-site workshop involving a small number of participants, which reduces the generalisability of the fi ndings.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…7 There is supportive literature on the usefulness of OB GYN US simulation that reveals it not only improves the scanning skills and detection rates of abnormal fi ndings but also helps providers to maintain their skills. [7][8][9][10] The results of our workshop suggest that virtual reality pelvic US simulation used in conjunction with didactics may improve the systematic approach in US scanning. A limitation of our study is that it refers to the outcomes of a single-site workshop involving a small number of participants, which reduces the generalisability of the fi ndings.…”
Section: Discussionmentioning
confidence: 91%
“…The new generation of high‐fidelity simulators provides an opportunity for the longitudinal monitoring of the learning curve and assessment of skills, potentially encouraging their use in accreditation and the validation of credentials . There is supportive literature on the usefulness of OB GYN US simulation that reveals it not only improves the scanning skills and detection rates of abnormal findings but also helps providers to maintain their skills …”
Section: Discussionmentioning
confidence: 99%
“…Similar studies performed for obstetric ultrasonography have drawn similar conclusions in terms of demonstrating construct validity, but have yet to show evidence of learning and improvement over time. 13 A recent study of transvaginal ultrasonography in gynaecology showed learning curves for novices reached an expert level after 3-4 h of simulation training. 14 A strong argument for the use of simulation training by novices is that nonexperts elicited a significantly higher number of audible sounds of distress from the simulator than experts.…”
Section: Discussionmentioning
confidence: 99%
“…The use of virtual models has also been studied for acquiring ultrasound skills. Burden et al 15 demonstrated construct validity for a virtual reality ultrasound simulator to develop skills in routine Ob imaging. A combined curriculum involving virtual reality models alongside live‐patient ultrasound examinations has been proposed as a more feasible and effective option for standardized training 16 .…”
Section: Discussionmentioning
confidence: 99%